Graphical abstract. - Ji-Xin Zhao (22056386) (2025)
Overview of the experimental design and major findings. Eighteen Sprague–Dawley rats were randomly divided into three groups: uninfected control (CON), acute infection (AI, day 7 post-infection), and chronic infection (CI, day 40 post-infection). Rats in the AI and CI groups were orally inoculated with 3,000 T. gondii PRU cysts, while controls received PBS. Small and large intestinal contents were collected for metagenomic sequencing, and serum was analyzed by untargeted metabolomics. The integrated multi-omics analysis revealed stage-specific alterations in gut microbial diversity, taxonomic composition, and functional potential, along with systemic metabolic perturbations. Spearman correlation analysis demonstrated coordinated associations between differential microbes and metabolites, illustrating the interaction network among T. gondii, the gut microbiota, and host metabolism. Created in BioRender. Jx, Z. (2025) https://BioRender.com/2rh0rbd. (TIF)